Frailty burden in older adults with type 2 Diabetes Mellitus and related factors (Research, Society and Development, 2020)
Aim: to determine the sociodemographic characteristics, clinica, functional and depressive symptoms related to the frailty burden in community-dwelling older adults with T2DM. Methods: observational, analytical cross-sectional study with diabetic older adults, aged ≥ 60 years, who are ambulatory and non-amputated. Sociodemographic characteristics, clinical-functional, and depressive symptoms and frailty phenotype were evaluated. A stepwise multivariate logistic regression analysis (p